An efficient quasi-3D rotordynamic and fluid dynamic model of Tilting Pad Journal Bearing. (November 2016) - Conti, R.; Frilli, A.; Galardi, E.; Meli, E.; Nocciolini, D.; Pugi, L.; Rindi, A.; Rossin, S.
Abstract: Over the last few decades the use of Tilting Pad Journal Bearings (TPJBs) has spread due to their better performances in the most demanding operating conditions (i.e. in the presence of high loads and speeds). This research paper describes the development and experimental validation of a new quasi-3D TPJB model, able to analyze both the fluid dynamics (also including the supply plant) and rotor dynamics of the system and their complex interactions. The developed model is characterized by a high numerical efficiency, thus allowing for complex simulation tasks, and strongly modular, with the possibility to easily represent different layouts of TPJBs. The proposed model has been developed and experimentally validated in collaboration with Nuovo Pignone General Electric S.p.a. considering a complete plant test rig which includes rotor, bearings and lubrication circuit. Finally, an innovative heuristic law is proposed in order to predict the TPJB fluid dynamical characteristics taking into account the coupled effects neglected by classical simplified models. Abstract : Graphical abstract: Abstract : Highlights: An innovative and efficient model of Tilting Pad Journal Bearings (TPJBs) is developed. The model contemporaneously describes the fluid dynamics of the system, the bearings lubrication and the lubricant supply plant. The model aims at obtaining a good compromise between accuracy and numerical efficiency. The model has been experimentally validated in cooperation with Nuovo Pignone General Electric S.p.a .